DNA methylation‐based biological aging and cancer risk and survival: Pooled analysis of seven prospective studies. Issue 8 (18th December 2017) - Dugué, Pierre‐Antoine; Bassett, Julie K.; Joo, JiHoon E.; Jung, Chol‐Hee; Ming Wong, Ee; Moreno‐Betancur, Margarita; Schmidt, Daniel; Makalic, Enes; Li, Shuai; Severi, Gianluca; Hodge, Allison M.; Buchanan, Daniel D.; et al.
Abstract : The association between aging and cancer is complex. Recent studies have developed measures of biological aging based on DNA methylation and called them "age acceleration." We aimed to assess the associations of age acceleration with risk of and survival from seven common cancers. Seven case–control studies of DNA methylation and colorectal, gastric, kidney, lung, prostate and urothelial cancer and B‐cell lymphoma nested in the Melbourne Collaborative Cohort Study were conducted. Cancer cases, vital status and cause of death were ascertained through linkage with cancer and death registries. Conditional logistic regression and Cox models were used to estimate odds ratios (OR) and hazard ratios (HR) and 95% confidence intervals (CI) for associations of five age acceleration measures derived from the Human Methylation 450 K Beadchip assay with cancer risk ( N  = 3, 216 cases) and survival ( N  = 1, 726 deaths), respectively. Epigenetic aging was associated with increased cancer risk, ranging from 4% to 9% per five‐year age acceleration for the 5 measures considered. Heterogeneity by study was observed, with stronger associations for risk of kidney cancer and B‐cell lymphoma. An associated increased risk of death following cancer diagnosis ranged from 2% to 6% per five‐year age acceleration, with no evidence of heterogeneity by cancer site. Cancer risk and mortality were increased by 15–30% for the fourth versus first quartile of age acceleration. DNA methylation‐based measures of biological aging are associated with increased cancer risk and shorter cancer survival, independently of major health risk factors. Abstract : What's new? Aging is associated with profound changes in DNA methylation levels. These can be used to build accurate age predictors ("epigenetic clocks") that deviate from chronological age by only a few years, a phenomenon named "age acceleration". In this study of seven types of cancer, the authors found that age acceleration was associated with both increased cancer risk and decreased cancer survival, independently of major health risk factors. These results support the usefulness of methylation markers of biological aging as a tool to predict health outcomes and may provide valuable insight into the relationship between aging and cancer.